Regulating the postharvest life of Campomanesia lineatifolia R. & P. fruits through the interaction of ethylene, 1-methylcyclopropene and low temperatures - González C., Angie Katherine; González-Martínez, Laura Fernanda; Córdoba, Luis David; Rincón P., Alfonso; Balaguera-López, Helber Enrique (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2021)
The champa (Campomanesia lineatifolia) is a very perishability berry with a pleasant taste. The objective of this research was to study the regulation and prolongation of the postharvest conservation of champa fruits using 1-methylcyclopropene (1-MCP) and refrigeration. Two experiments were carried out: In experiment 1, four treatments were evaluated to understand the regulation of maturation. The treatments were: control, 1-MCP, ethylene and 1-MCP + ethylene. The fruits were stored at room temperature. In experiment 2, the combination of the application of 1-MCP and two storage temperatures (room temperature [16±2°C] as well as 2±0.4°C) were used. In the two experiments, four repetitions were used, each one with approximately 500 g of fruits harvested at stage 2 of maturity (25% yellow and 75% green). The results of experiment 1 indicated that the fruits with 1-MCP presented the longest postharvest duration (17 days), firmness, and titratable acidity. They also had the lowest respiratory rate and weight loss during the 10 days. However, the fruits treated with ethylene had the opposite behavior, indicating that the changes evaluated during ripening were associated with this hormone. In experiment 2, the fruits refrigerated at 2°C, with or without the application of 1-MCP, had the longest postharvest duration, lasting 26 days, as compared to 12 days in the control fruits (without refrigeration and with 1-MCP). The fruits that lasted longer had a low respiratory rate during storage, as well as lower values for weight loss and, color index but, greater firmness and acidity. The 1-MCP was efficient when the fruits were at room temperature.